The Subjectivity of Nawāl Al-Sa’dāwī: Critique on Gender Relations in Religious Construction in Adab Am Qillah Adab Work - Yulia Nasrul Latifi; Wening Udasmoro; Juliasih J. (Al-Jami'ah: Journal of Islamic Studies, 2019)
This writing examines three short stories in the short story anthology of Adab Am Qillah Adab by Nawāl Al-Sa’dāwī, namely: “Adab.Am Qillah Adab”, “al Umm al-Suwisriyyah al-Qātilah”, and “Qiṣṣah Fatḥiyyah al-Miṣriyyah”. The analysis focuses on Nawâl al-Sa’dâwî’s critique of religious constructions of gender relations. The subjectivity of Salvoj Žižek is the theory used and hermeneutics is the method of analysis. The purpose of the study is to find out the reasoning behind the radical acts of Al-Sa’dāwī over her rejection of patriarchal religious constructions in her three short stories. The result of the analysis shows that the literary work is the explanation of the radicalization of the author’s actions, Al-Sa’dāwī, as a subject. Such radicalization is her rejection of the needy Symbolic (patriarchal religion construction) as her attempt to escape the Symbolic. Al-Sa’dāwī continues to move because the subject is split and empty. Therefore, Al-Sa’dāwī makes an effort to seek full self-fulfillment to and approach The Real in order to kill the old tyrannical Symbolic and pick up the new Symbolic, which is the construction of a just religion and liberate women.[Tulisan ini mengkaji tiga cerpen dalam antologi cerpen Adab Am Qillah Adab karya Nawâl al-Sa’dâwî, yaitu: “Adab..Am Qillah Adab”, “al-Umm al-Suwisriyyah al Qātilah”, dan “Qiṣṣah Fatḥiyyah al-Miṣriyyah”. Analisis difokuskan pada kritik Nawāl Al-Sa’dāwī terhadap konstruksi agama atas relasi gender. Subjektivitas Salvoj Žižek adalah teori yang dipakai dan hermeneutik merupakan metode analisisnya. Tujuan penelitian adalah untuk mengetahui alasan di balik tindakan radikal Al-Sa’dāwī atas penolakannya pada konstruksi agama yang patriarkis dalam tiga cerpennya. Hasil analisis menunjukkan bahwa karya sastra menjelaskan radikalisasi tindakan pengarang, Al-Sa’dāwī, sebagai sebuah subjek. Radikalisasi tersebut adalah penolakannya terhadap Yang Simbolik yang berkekurangan (konstruksi agama patriarkis) sebagai usahanya untuk melepaskan diri dari Yang Simbolik. Al-Sa’dāwī akan terus bergerak dikarenakan subjek itu terbelah dan juga kosong. Oleh sebab itu, Al-Sa’dāwī melakukan upaya untuk mencari pemenuhan dirinya secara terus-menerus dan mendekati The Real agar dapat membunuh The Symbolic lama yang tiranik dan menjemput The Symbolic baru, yaitu konstruksi agama yang adil dan membebaskan perempuan.]